Identification of Heat Shock Protein 90 as a Recurrence Related Marker in Juvenile Nasopharyngeal Angiofibroma. Issue 1 (January 2022) - Wang, Jingjing; Hu, Li; Liu, Zhuofu; Wang, Huan; Zhang, Huankang; Song, Xiaole; Sun, XiCai; Wang, DeHui
Background: Juvenile nasopharyngeal angiofibroma (JNA) is a highly recurrent tumor after curative surgery. Objective: The purpose of this study was to evaluate heat shock protein 90 (HSP90) expression in JNA and its association with tumor recurrence. Methods: Immunohistochemistry was performed to assess HSP90 expression using tissue microarrays containing 70 JNA patients and 10 control subjects. The associations of HSP90 expression with clinicopathological features and tumor recurrence were analyzed. Results: Immunohistochemistry revealed high HSP90 expression in JNA compared with normal middle turbinate samples. High expression of HSP90, which correlated with MVD ( P  = .001), ER-α ( P  = .001), VEGF ( P  < .001) and JNA recurrence ( P  = .009), was an independent prognostic factor of time to recurrence ( P  = .017). The combination of HSP90 and ER-α had a better power to predict disease recurrence than other clinicopathological features ( P  = .008). Conclusions: HSP90 may be an independent prognostic marker in JNA patients administered surgical treatment. Combination of HSP90 and ER-α expression may be the best predictor of tumor recurrence among all clinicopathological factors.